Understanding the effects of cofactor Ufd1 and Actin binding to p97 - Sim, Benjamin Kunyi (2016)
p97/Valosin-containing protein (VCP) is a member of the AAA-ATPase family and it is involved in a diverse range of cellular activities such as protein degradation and membrane reformation pathways. The highly conserved ATPase functions as a homohexamer and the key to its multifunctionality lies within its arsenal of cofactors. Different cofactors can engage p97/VCP in a particular function and direct it to distinct cellular pathways. Recent findings by our lab found that p97/VCP-knockdown cells displayed an aberrant actin structure characterised by heavy polymerisation of actin filaments. As a major cofactor of p97/VCP, Ufd1 was also found to have decreased binding affinity to p97/VCP while binding affinity between p97/VCP and actin was increased. Nonetheless, the involvement of the interaction between p97/VCP and cofactor Ufd1 in actin regulation remains unclear. Hence, this project aims to determine the role of the interaction between p97/VCP and Ufd1 in actin regulation and to investigate if Ufd1 and actin binds to p97/VCP in a mutually exclusive manner. Results obtained showed that the reduction of cofactor Ufd1 levels did not affect actin morphology significantly. The co-immunoprecipitation experiment conducted may require further optimisation to fully elucidate the mutually exclusive relationship between Ufd1 and actin in binding p97/VCP.